The future of graduates in the global labour market - Lauder, Hugh (My University, 2015)
Dear Minister, colleagues and distinguished guests! Thank you very much for inviting me to give this keynote this morning in these challenging circumstances that we face. Let me also say that it is rare that I have had a Minister of Education with whom I have agreed so wholeheartedly as in this particular case. I think the message here is one, which is actually very pertinent to what I have to say. I would also like to say that this university, I understand, is meant to be a model for the practices of higher educational institutions in this country. I think this particular conference is a model for the rest of the world as well. I have not been to a conference where I have seen the combination of academics, employers and those people who are trying to bring the two together – practitioners in that sense, but in a conference of this size and with so many guest speakers. I thank you very much for inviting me along for this conversation. The message I have to give today is one, which I hope, will set out the challenge and I shall overemphasize it, that means that I shall be polemical and I hope it will provoke some discussion.
Keywords: EHELF; Eurasian Higher Education Leaders’ Forum